Peptide vaccination against cytomegalovirus induces specific T cell response in responses in CMV seronegative end-stage renal disease patients - Sommerer, Claudia; Schmitt, Anita; Hückelhoven-Krauss, Angela; Giese, Thomas; Bruckner, Thomas; Wang, Lei; Schnitzler, Paul; Meuer, Stefan; Zeier, Martin; Schmitt, Michael (Vaccines, 2021)
Introduction: Cytomegalovirus (CMV) reactivation occurs in seronegative patients after solid organ transplantation (SOT) particularly from seropositive donors and can be lethal. Generation of CMV-specific T cells helps to prevent CMV reactivation. Therefore, we initiated a clinical phase I CMVpp65 peptide vaccination trial for seronegative end-stage renal disease patients waiting for kidney transplantation. Methods: The highly immunogenic nonamer peptide NLVPMVATV derived from CMV phosphoprotein 65(CMVpp65) in a water-in-oil emulsion (Montanide™) plus imiquimod (Aldara™) as an adjuvant was administered subcutaneously four times biweekly. Clinical course as well as immunological responses were monitored using IFN-γ ELISpot assays and flow cytometry for CMV-specific CD8+ T cells. Results: Peptide vaccination was well tolerated, and no drug-related serious adverse events were detected except for Grade I-II local skin reactions. Five of the 10 patients (50%) mounted any immune response (responders) and 40% of the patients presented CMV-specific CD8+ T cell responses elicited by these prophylactic vaccinations. No responders experienced CMV reactivation in the 18 months post-transplantation, while all non-responders reactivated. Conclusion: CMVpp65 peptide vaccination was safe, well tolerated, and clinically encouraging in seronegative end-stage renal disease patients waiting for kidney transplantation. Further studies with larger patient cohorts are planned.